АЙРИМ РИВОЖЛАНГАН МАМЛАКАТЛАРДА ҲОКИМИЯТ БЎЛИНИШИГА ДОИР ФАЛСАФИЙ ҚАРАШЛАР - Жўрақулов, Ф.Н. (SCIENCE and SOCIETY, 2018)
The article is devoted to the study of various forms of khakimiat on the example of the state structure in the developed countries the author analysed, the philosophical points of view to this issue. The building of the society in Uzbekistan has been studied comparatively with laws of the state structure.
Keywords: khakimiyat; subjects; lawyer; doer; court activity; civic society; economist; sociologist; liberalism